Decisions of the Comptroller General of the United States - United States. General Accounting Office; United States. General Accounting Office. Office of the General Counsel (Washington, D.C. : G.P.O., 1927)
Contains a selection of major decisions of the GAO. A digest of all decisions has been issued since Oct. 1989 as: United States. General Accounting Office. Digests of decisions of the Comptroller General of the United States. Before Oct. 1989, digests of unpublished decisions were issued with various titles.
Includes index.
Microfiche.
Vols. for July 1, 1921-June 30, 1922-<Oct. 1, 1985-Sept. 30, 1986> issued by: U.S. General Accounting Office; <Oct. 1, 1987-Sept. 30, 1988-> issued by: U.S. General Accounting Office, Office of General Counsel.
Scope line index: Vols. 1 (July 1, 1921)-46 (June 30, 1967), 1 v.; Vols. 46 (1966)-50 (1971), 1 v.; Vols. 51 (1971)-55 (1976), 1 v.
Indexed by: United States. General Accounting Office. Index to the published decisions of the accounting officers of the United States, 1921-1929; and: United States. General Accounting Office. Index digest of published decisions of the Comptroller General of the United States, 1929-
Cumulation of the monthly: United States. General Accounting Office. Decisions of the Comptroller General of the United States; which is in turn a cumulation of: Decisions of the Comptroller General of the United States. Advance sheets.
Keywords: United States. -- General Accounting Office -- Periodicals; Finance, Public -- United States -- Accounting -- Periodicals; Government property -- United States -- Periodicals; United States -- Appropriations and expenditures -- Periodicals